2019
DOI: 10.1093/nop/npz052
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment after cytotoxic chemotherapy

Abstract: Background Neurotoxicity is a frequent side effect of cytotoxic chemotherapy and affects a large number of patients. Despite the high medical need, few research efforts have addressed the impact of cytotoxic agents on cognition (ie, postchemotherapy cognitive impairment; PCCI). One unsolved question is whether individual cytotoxic drugs have differential effects on cognition. We thus examine the current state of research regarding PCCI. Neurological symptoms after targeted therapies and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
0
24
1
1
Order By: Relevance
“…Unlike other studies, in the current study, there was no association between MMSE cognitive score and the number of chemotherapy cycles taken, type of chemotherapy regimen, and the stage of breast cancer (21)(22)(23). This may be due to differences in the method of cognitive assessment used and the difference in disease and treatment status of the patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Unlike other studies, in the current study, there was no association between MMSE cognitive score and the number of chemotherapy cycles taken, type of chemotherapy regimen, and the stage of breast cancer (21)(22)(23). This may be due to differences in the method of cognitive assessment used and the difference in disease and treatment status of the patients.…”
Section: Discussioncontrasting
confidence: 95%
“…This report was not included in our analysis because it was not limited to taxanes but included other agents such as vinca alkaloids, anthracyclines, platinum compounds, topoisomerase inhibitors, and bleomycin and mitomycin (66). In addition, this report did not subdivide the cognitive changes into domains, but rather showed overall decreased cognitive function (66). Nonetheless, a similar pattern of CICI was reported compared with that which we observed.…”
Section: Discussionmentioning
confidence: 66%
“…In 2019, a systematic review investigating cognitive impairment after cytotoxic chemotherapy examined 21 studies with enrolled patients with breast cancer (66). This report was not included in our analysis because it was not limited to taxanes but included other agents such as vinca alkaloids, anthracyclines, platinum compounds, topoisomerase inhibitors, and bleomycin and mitomycin (66). In addition, this report did not subdivide the cognitive changes into domains, but rather showed overall decreased cognitive function (66).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on cognitive impairment after cytotoxic chemotherapy demonstrated that two out of three studies on colon cancer treated with FOLFOX had not observed cognitive changes, whereas 21 out of 25 studies on breast cancer had detected cognitive impairment after cytotoxic chemotherapy. [21] The findings imply that characteristics of primary tumor, both biological and psychosocial, play important role on manifestation of chemotherapy-related cognitive impairment. It is well known that a significant proportion of breast cancer patients suffer from depression and anxiety, which leads to dysfunctional cognition and general fatigue.…”
Section: Discussionmentioning
confidence: 98%